Parasitoids and its importance in biological control of pest - Sucheta Prakash (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2010)
The temperature has an important impact on the parasitoid’s biological traits in a lab setting, suggesting that the effectiveness of a biological control programme may be impacted by this factor. However, the use of additional synthetic insecticides became vital for both the effectiveness of Integrated Pest Management and biological control programmes. However, aside from parasitoid species that reside on the exact same host, parasitoid wasps that are focused on herbivores often do not have the ability to attack other guild mates.In terms of eradicating their carriers, parasitic organisms are the most effective natural enemies in biological insect control.Therefore, it is crucial to correctly identify the hosts and parasitoid subspecies when utilising parasitoids for biological control. Biological control is the effective management of pests and the damage they cause by parasites, diseases, and predators. Effective biological control requires accurate pest identification that separates pests from their natural adversaries.